DEVELOPMENT OF AN INNOVATIVE TECHNICAL SOLUTION FOR THE APPLICATION OF SEGMENTAL MANAGAN INSERTS ON THE WEAR SURFACE OF THE CLAMP OF THE TAMPING RAILWAY MACHINES - Veljko Vuković; Sergiy Kovalevskyy (Advanced Engineering Letters, 2024)
Research in this paper is focused on defining the appropriate methodology of integrated product development in the process of constructing and practical application of replaceable segments that are installed on the working surface of the rail construction tamping machine. The research presents an innovative solution of segmental cast inserts made of special alloyed steel with manganese as the alloying element. The specially designed segment of the clamp is a spare part that requires timely replacement to ensure optimal operation of the machine and more extended exploitation. In the paper, the innovative solution was compared with the traditional maintenance procedure by hardfacing a layer on the worn surface of the clamp. The innovativeness of the proposed technological procedure for the maintenance of clamps is reflected in the better reliability, i.e. the extension of the shelf life by up to 4.5 times and the reduction of maintenance by 40.62 times compared to the traditional method of reparative hardfacing. Efficiency, as a key factor in maintenance, is reflected in the fact that, with an inventive solution, the replacement of worn segmental inserts can be done in the field without the need to demobilize the tamping machine and send it to the workshop.